Penetapan Pengakuan Dan Perlindungan Masyarakat Hukum Adat Di Kabupaten Maluku Tengah - Lainsamputty, Natanel (Jurnal Saniri, 2022)
Central Maluku Regency is the oldest district in Maluku Province which has a customary law community unit called the Negeri, in the regulation of the Village Law, it is mandatory to organize villages into villages and customary villages. Before the determination of customary villages and villages is carried out, it is necessary to determine the recognition and protection of customary law communities, because it is a requirement to be established as a customary village. The research method used in this paper is normative research with a statutory approach as primary data and also by using concepts, theories as library materials which are secondary data to analyze the problem of establishing the customary law community unit in Central Maluku. The results of this study indicate that until now there has not been a determination of the recognition and protection of indigenous peoples in Central Maluku, this also has an impact on the stipulation of the Negeri as a traditional village in Central Maluku